2021
DOI: 10.1080/13696998.2021.1901721
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of axicabtagene ciloleucel versus tisagenlecleucel for adult patients with relapsed or refractory large B-cell lymphoma after two or more lines of systemic therapy in the United States

Abstract: To assess from a US payer perspective the cost-effectiveness of the chimeric antigen receptor T (CAR T)-cell therapies axicabtagene ciloleucel (axi-cel) and tisagenlecleucel (tisa-cel) to treat relapsed or refractory (r/r) large B-cell lymphoma (LBCL) following ≥2 systemic therapy lines. Methods A 3-state (i.e., pre-progression, post-progression, death) partitioned survival model was used to estimate the quality-adjusted life-years (QALYs) and costs for patients on each treatment over a lifetime horizon. Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Other possibly relevant AEs, such as cytopenias or infections, were excluded from the analysis. Furthermore, no disutility values were attributed to AEs similar to other economic evaluations developed for axi-cel [14,16].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Other possibly relevant AEs, such as cytopenias or infections, were excluded from the analysis. Furthermore, no disutility values were attributed to AEs similar to other economic evaluations developed for axi-cel [14,16].…”
Section: Discussionsupporting
confidence: 58%
“…Recently, a cost-utility analysis developed from the USA payer perspective for the same comparators presented axi-cel as a dominant alternative vs. tisa-cel, resulting in higher QALY gained (+2.31 discounted) and slightly lower costs (−$1407) [14]. QALY gained for axi-cel vs. tisa-cel were equal from USA and Spanish payer perspectives, however total costs were higher for tisa-cel in the USA analysis, in contrast with our analysis where axi-cel showed higher costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analyses have been recently conducted to evaluate the cost‐effectiveness and budget impact of anti‐CD19 CAR‐T therapies from a US‐payer perspective. Anti‐CD19 CAR‐T therapy cost $373 000 for a one‐time infusion, not accounting for expenses associated with hospitalizations, ICU stays, and treatment of toxicities while the estimated cost of salvage chemotherapy and HCT range between $145 000 and $195 000 17–19 …”
Section: Discussionmentioning
confidence: 99%
“…CAR T cell treatment costs were modeled according to observed hospitalization data from the JULIET trial as reported in Yang et al 22 Inpatient and ICU costs were calculated separately. 23 Adverse event costs were estimated based on grade 3 or greater adverse events with incidence rates greater or equal to 5%, including cytokine release syndrome and neurotoxic effects (eTable 2 in Supplement 1). CAR T cell therapy travel-related out-of-pocket costs were reported to be different across settings and thus were included as informal costs.…”
Section: Model Parametersmentioning
confidence: 99%